دور اتخاذ القرارات الادارية في تحقيق الميزة التنافسية دراسة ميدانية في المصارف غير الحكومية العراقية - خالد عبد الله إبراهيم (مجلة الغري للعلوم الاقتصادية والادارية)
المستلخص: یهدف هذا البحث الى التعرف على أهمیة اتخاذ الق ا ر ا رت الإداریة في المصارف غیر الحكومیة الع ا رقیة وخصوصا مصرف بغداد وما هي الحلول المبتكرة التي تواجه التحدیات التي تتعرض لها المصارف من خلال المنافسة وبما یتماش وسیاسة الجودة المعتمدة لدیها . كما یهدف البحث الى تقدیم النتائج والتوصیات التي یمكن الاسترشاد بها في اتخاذ الق ا ر ا رت الإداریة لتحقیق جودة الخدمات المصرفیة واستغلالها كفرص نحو التقدم والنجاح . وباستخدام الاختبا ا رت الإحصائیة المناسبة توصلت الد ا رسة الى عدد من النتائج كان من أهمها ان الزبائن المستفیدین من الخدمات المصرفیة لدیهم ثقة بالمصرف عینة الد ا رسة لقدرتهم على انجاز الخدمات المصرفیة العالیة الجودة. وعلى ضوء النتائج خلصت الد ا رسة الى عدد من التوصیات كان من أهمها ضرورة تبني المصرف لتحقیق الأهداف ومنافسة المصارف (Iso لنظم إدارة الجودة وتطبیق كامل لمتطلبات ( 9001:2008 الأخرى وتحسین الخدمات المصرفیة وفقا لمتطلبات ورغبات المستفیدین من الخدمات المصرفیة في ضوء الق ا ر ا رت الإداریة المتخذة من قبل مجلس إدارة المصرف عینة الد ا رسة . Abstract This research aims to identify the importance of managerial decisionmaking in non-Iraqi government banks, particularly the Bank of Baghdad and what are the innovative solutions that meet the challenges faced by the banks through competition and in full conformity and quality policy accredited to it .The research also aims to provide findings and recommendations that can guide management decisions to achieve the quality of banking services and exploited as opportunities to progress and success And using appropriate statistical tests the study found a number of the most important findings was that the beneficiaries of banking customers have confidence in the bank study sample of their ability to accomplish high quality banking services. In light of the study concluded that a number of the recommendations was the most important need for the adoption of the bank to quality management systems and full implementation of the requirements of (Iso 9001: 2008) to achieve the goals and compete with other banks and improve banking services according to the requirements and desires of the beneficiaries of banking services in the light of the administrative decisions taken by the Board of Bank management study sample.